CHIPPING TECHNIQUE FOR NON-UNIONS AND/OR DEFORMITY CORRECTION - Matsushita, Takashi (International Journal of Allied Health Sciences, 2021)
My chipping technique was originally developed for treatment of non-unions. However, I have found that in many cases of non-unions with deformities, deformities have been corrected very well simultaneously when I apply chipping technique to treat non-unions. Therefore, I started to use this chipping technique to correct deformities without non-unions. Open or closed wedge osteotomy is widely used to correct angular deformities. Closed wedge osteotomy requires precise angular osteotomy and open wedge osteotomy requires bone graft. Using my chipping technique, any angular and/or rotational deformity can be corrected accurately without precise wedge osteotomy. Furthermore, bone healing is quick and sure, because the chipping technique was originally developed to treat non-unions. The chipping technique could be a better alternative to wedge osteotomy for deformity correction. Additionally, as lots of callus is formed at chipped site, the callus can be lengthened using Ilizarov technique in case of shortening deformities. Chipping and lengthening technique, which requires neither precise osteotomy nor bone grafting, can be a useful technique for any deformities including shortening.